Optimizing the Supply Chain in a Fuel Process Industry (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Supply Chain Improvement (SCO) project is being introduced by KNPC, which recognises the major business advantages of improved hydrocarbon supply chain efficiency. The objectives of this work is to strengthen, optimise, and integrate supply scheduling and processes not just at stage of enterprise, but also throughout the entire KNPC framework. This is expected to lead to an improvement in the company's bottom line and facilitate the management of business operations at the highest level of efficiency, agility and profitability. In ever changing market conditions and globally competitiveness, it is necessary that raw material supply storage and product delivery were carried out at the lowest possible time and efficiency. Otherwise export oriented refinery like KNPC cannot remain in business with profit. KNPC has therefore embarked on ambitious multi-year operational excellence programs aimed at enhancing its operations and business processes that include short / mid-term planning, scheduling, accounting for growth, inventory management, and performance management. The aim is to achieve top-quartile financial results by accessing new value streams, encapsulating business processes of best practice and motivating employees of businesses to work in a collaborative atmosphere within the global and cross-functional business cycle to make smarter, quicker and more competitive choices.